Study of Association of gene polymorphism with nutrition and nutritional status of martial arts athletes - E. Yu. Sorokina; A. V. Pogozheva; D. B. Nikityuk (National Electronic Information Consortium (NEICON), 2020)
Objective: studying the effect of genetic polymorphisms: rs1815739 (ACTN3 gene), rs2016520 (PPARD gene), rs1042713 (ADRB2 gene), rs1799945 (HFE gene) on anthropometric and lipid metabolism indicators in athletes representing martial arts. Materials and methods: studies of anthropometric and biochemical parameters, genetic polymorphisms were carried out in 83 athletes (64 men and 19 women) who were are engaged in martial arts. Anthropometric studies were performed by height (cm) and body weight (kg) measuring followed by calculating body mass index (BMI, kg / m2). Biochemical nutritional status markers were determined using the ABXPENTRA 400 analyzer (HORIBA ABX SAS, France) in an automatic mode. Genotyping was performed using allele-specific amplification using TaqMan probes complementary to polymorphic DNA regions and realtime detection of the results using reagent kits from Syntol, Russia. Studies were performed on the device «CFX96 Real Time System» («BIO-RAD», USA). Statistical processing of the results was performed using the PASW Statistics 20 system. Results: as a result of gene testing for endurance of combat athletes, it was found that the frequency of the T allele of the rs1815739 polymorphism (ACTN3 gene) was 47.5%, the PPARD gene ал20120120 allele G is 13.9%, the rs1042713 G allele of the ADRB2 gene was 51.9%, and the G allele of the rs1799945 polymorphism of the HFE gene was 19.3%. No association was found between the value of anthropometric parameters in athletes and the presence of the studied polymorphisms. Conclusions: the cause of identified dyslipidemia in combat athletes may be not only the disturbances in the structure of their nutrition that we found earlier, but also the presence of certain genetic polymorphisms.